Know Your People: Social Research and Water Recycling System Design with Communities in the Amazon - Davis, M.J.M. (2016)
This paper sets out to answer the research question: What differences come about when water-recycling strategies are adapted to the local cultural context? It is argued that water management systems should be circular metabolisms, where wastewater is mobilized as a nutrition source. The aim is to propose water-recycling strategies at a micro level that reflect this. However, water-recycling systems are dependent on a complex set of social factors as to their acceptance/refusal and correct/incorrect use by the end users. This is particularly the case in Ecuador, where a plethora of variations in climates and cultures means that each project is different. This study proposes a qualitative methodology for the development of water-recycling strategies, where semi-structured interviews are first carried out to determine the design parameters of the specific social context where the project is to be implemented. Based on this, a water-recycling system can be proposed that is more likely to be readily accepted by the end users. The paper works with four of case studies, where the methodology is applied in three rural communities and an urban suburb in the Napo province of Ecuador, located in the Amazonian region. The results show that there were distinct differences in the water recycling strategies that were considered most appropriate for each case study. As such participatory design approaches can be said to be of great importance in the design of water-recycling strategies, where further work would necessary in working with the community members for the final system design.